Treatment of copper contaminated soil using ladle furnace slag - Chew, Siew Hong (Nanyang Technological University, 2021)
The increase in industrial activities leads to copper (Cu)-contaminated soils. The Cu-contaminated soil could leach into the groundwater or surface water and harms humans. Ladle Furnace Slag (LFS) is a by-product generated from the secondary steelmaking process. Currently, LFS is generally disposed of in landfills and could harm the environment as it comprises of different chemicals compound. The objective of this research is to use LFS as a binder for Solidification/stabilization (S/S) of Cu-contaminated soil. In order to investigate the effectiveness of LFS for reducing the leaching of Cu from Cu-contaminated soil. Conventional curing and carbonation are used in this study. For conventional curing, the prepared samples are cured for 3 hours, 7 days, and 28 days. For carbonation, the samples are carbonated for 2, 8, 32, and 56 hours. Both the cured and carbonated Cu-contaminated soils are then subjected to Unconfined Compressive Strength test (UCS), leaching tests, X-Ray Diffraction analysis (XRD), and Field Emission Scanning Electron Microscope (FESEM) with Energy Dispersive X-Ray analysis (EDX). The results show that both conventional curing and carbonation are effective in immobilizing Cu in LFS-stabilized Cu-contaminated soils. The leached concentration of the sample for both methods is below the limits of inert waste (EUR-Lex, 2002) and the United States Environmental Protection Agency (USEPA) drinking water standards (USEPA, 2018). For conventional curing, the leached concentration decreases with the increase of curing time. While the UCS increases with the increase of curing time and initial concentrations, having the highest strength of 127.5 kPa. From XRD and FESEM analysis, Calcium Silicate Hydrate (CSH) and Calcium Aluminum Silicate Hydrate (CASH) are detected after 28 days of curing. For carbonation, the leached concentration is slightly higher than that with conventional curing, but it is still effective in reducing the leaching of Cu. The UCS increases with the increase of initial concentrations, with the highest strength of 87.6 kPa. The XRD and FESEM analysis show the presence of Copper Carbonate (CuCO3), Calcite (CaCO3), Nesquehonite (MgCO33H2O), and Hydromagnesite (4MgCO3Mg(OH)24H2O) after carbonating for 56 hours. The presence of these minerals could help to enhance strength and reduce leaching. Both methods are effective in immobilizing the leaching of Cu-contaminated soil. Factors such as time, cost, and environmental considerations can affect the choice of method.